Planning for Climate Change in South Florida: Climate Envelope Modeling for Threatened and Endangered Species - Laura A. Brandt; Stephanie S. Romañach; Frank J. Mazzotti (EDIS)
WEC282, a 3-page illustrated fact sheet by Laura A. Brandt, Stephanie S. Romañach, and Frank J. Mazzotti, describes a project of the University of Florida, U.S. Fish and Wildlife Service, U.S. Geological Survey, and National Park Service to develop methods and tools that will allow natural resource managers to examine potential effects of climate change on species’ geographic ranges in the context of ecosystem and landscape planning in South Florida. Published by the UF Department of Wildlife Ecology and Conservation, April 2010.